Evaluation of COVID-19 risk in patients on systemic retinoid therapy - Emine Müge Acar; Kemal Özyurt; Rukiye Akyol (Galenos Publishing House, 2022)
Background and Design: Systemic retinoids are commonly used medications in dermatology and indicated in various skin disorders such as acne vulgaris and psoriasis. Data about the risk of Coronavirus disease-2019 (COVID-19) in patients using systemic retinoids are limited. Thus, this study aimed to investigate the risk of COVID-19 in patients undergoing systemic retinoid therapy. Materials and Methods: A total of 186 patients who have undergone systemic isotretinoin and acitretin therapy were recruited. Patients who presented to the dermatology clinic for various skin diseases, such as eczema, vitiligo, tinea, etc., who were not on systemic retinoid therapy, and who received topical medications comprised the control group. The development of COVID-19 in the retinoid therapy group and the control group was retrospectively reviewed using hospital database. Results: The mean age of the patients in the retinoid therapy group was 25.72+-0.67 and that in the control group was 25.4+-0.62. Moreover,165 patients received isotretinoin, and 21 patients received acitretin treatment. The isotretinoin dosage ranged from 0.5 to 0.8 mg/kg wheras the acitretin dosage ranged between 10 and 25 mg/day. Two patients (1.07%) in the retinoid therapy group and 8 (4.3%) patients in the control group were diagnosed with COVID-19. None of the patients receiving acitretin was diagnosed with COVID-19. COVID-19 diagnosis was established in the 2nd and 3rd months of isotretinoin treatment, and lung involvement was not observed. No significant difference regarding the number of COVID-19 cases and disease severity was found between the two groups (p=0.105; p=0.258, respectively). Conclusion: Isotretinoin and acitretin use was not associated with increased COVID-19 risk or disease severity. Systemic retinoids appear to be a safe treatment modality in the COVID-19 era.